A Li-rich strategy towards advanced Mn-doped triphylite cathodes for Li-ion batteries. (17th January 2023) - Nazarov, Eugene E.; Dembitskiy, Artem D.; Trussov, Ivan A.; Tyablikov, Oleg A.; Glazkova, Iana S.; Alexey, Sobolev V.; Presniakov, Igor A.; Mikheev, Ivan V.; Morozov, Anatolii V.; Nikitina, Victoria A.; Abakumov, Artem M.; Antipov, Evgeny V.; et al.
Abstract : Introduction of additional Li ions into the LiFe0.5 Mn0.5 PO4 crystal structure results in an extended solid solution region of the Li + de/intercalation process. Abstract : Triphylite-structured lithium iron/manganese phosphates have captured rapt attention as prospective positive electrodes for Li-ion batteries, targeted to automotive applications. Here we report on a strategy to improve the power characteristics of Mn-doped LiFePO4 cathode materials by introducing extra Li at the transition metal site (Li-rich) via a facile solvothermal synthesis route. The crystal structure refinement based on joint synchrotron and neutron powder diffraction data unambiguously confirmed the formation of a Li-rich phase, with additional validation coming from scanning transmission electron microscopy, electron energy loss spectroscopy, and 57 Fe Mössbauer spectroscopy. The particularly created defect structure of the Li-rich Li1+ δ (Fe0.5 Mn0.5 )1− δ PO4 with additional Li + ions residing at the 3d-metal site enables the extended solid solution region of the Li ion de/intercalation mechanism established using operando synchrotron X-ray powder diffraction. The suggested strategy offers an advanced electrochemical behavior of the materials that exhibit specific capacities of over 158 mAh g −1 at C/10 and 120 mAh g −1 at 10C, with retention of 84 ± 4% after 500 cycles at 10C.